2019
DOI: 10.1038/s41467-019-09607-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelets in mediating a response to human influenza infection

Abstract: Influenza infection increases the incidence of myocardial infarction but the reason is unknown. Platelets mediate vascular occlusion through thrombotic functions but are also recognized to have immunomodulatory activity. To determine if platelet processes are activated during influenza infection, we collected blood from 18 patients with acute influenza infection. Microscopy reveals activated platelets, many containing viral particles and extracellular-DNA associated with platelets. To understand the mechanism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
267
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(298 citation statements)
references
References 64 publications
7
267
2
6
Order By: Relevance
“…This was the first study to present real laboratory data to confirm other reports on the mechanism of platelet inhibition induced by influenza virus. It has been reported that influenza virus could induce uncontrolled platelet activation to fuel a harmful inflammatory response in the respiratory tract . We hypothesized that such excessive activation of platelets by influenza virus may lead to a markedly decreased platelet count compared with other respiratory tract infections.…”
Section: Discussionmentioning
confidence: 97%
“…This was the first study to present real laboratory data to confirm other reports on the mechanism of platelet inhibition induced by influenza virus. It has been reported that influenza virus could induce uncontrolled platelet activation to fuel a harmful inflammatory response in the respiratory tract . We hypothesized that such excessive activation of platelets by influenza virus may lead to a markedly decreased platelet count compared with other respiratory tract infections.…”
Section: Discussionmentioning
confidence: 97%
“…Capillary thrombosis is described as one of the main features in the 1918 pandemic influenza (Taubenberger & Morens, 2008) and was also observed in the 2009 pandemic (Bunce et al, 2011). Recently, IAV particles were detected within platelets from patients infected with IAV H1N1, H3N2 and IBV, potentially taken up by phagocytosis (Koupenova et al, 2019).…”
Section: Platelet Activationmentioning
confidence: 99%
“…Thus, thrombocytopaenia may reflect (a) alteration in thrombopoiesis due to the bone marrow or lungs (and potentially spleen) being inflamed or receiving inflammatory and trauma-related thrombopoietic cues; (b) localised lung recruitment of platelets as a facet of their role in the immune response or alveolar coagulation; (c) disseminated intravascular coagulation (DIC) throughout the body (Xu, Zhou, & Xu, 2020); or (d) platelet-viral interaction, although this remains hypothetical as an engagement of platelets with SARS-CoV-2 has not been described (Amgalan & Othman, 2020 Results of studies in mice modelling influenza agree on the necessity for platelets in the immune response and inflammation but conflict as to whether this is beneficial (Campbell et al, 2019;Guo et al, 2017), or detrimental (Boilard et al, 2014;Lê et al, 2015). Additionally, platelets respond to influenza virus by increasing complement availability and encourage the release of NETs into blood, and so platelets may be important integrators linking viral infection to neutrophil responses that are associated with coagulopathy and venous thrombosis (Koupenova et al, 2019). Furthermore, platelets have a complex relationship with lung inflammation in that they can be both protective of the alveolar capillary barrier or can promote excessive vascular leak (Middleton, Rondina, Schwertz, & Zimmerman, 2018;Weyrich & Zimmerman, 2013).…”
Section: Platelet Responses Coagulopathy and Hyperinflammationmentioning
confidence: 99%